Analysis of Calcium (Ca) and Potassium (K) Levels in Mackerel (Rastrelliger sp.) Bones - Ni Luh A. Murtini; Baharuddin Hamzah (Universitas Tadulako, 2020)
Mackerel (Rastrelliger sp.) is one of the potential pelagic fish in Indonesia and in almost all Indonesian waters. In general, fish bones contain many essential ingredients for the body and can be processed into fish bone flour. This study aimed to determine calcium (Ca) and potassium (K) levels in mackerel (Rastrelliger sp.) bones. Calcium and potassium levels were determined using an atomic absorption spectrophotometry (AAS). Results of the analysis showed that the water, ash, and biomass levels of the sample were 10.53, 18.26, and 71.21%, respectively. Analysis of calcium and potassium levels at wavelengths 422.7 nm and 766.5 nm obtained an average of 508.15 and 36.37 mg/100g. The results indicate that the calcium level is higher than the potassium level in mackerel (Rastrelliger sp.) bones.